The Threat of Social Media Propaganda on the Existence of the Papuan Student Movement in Supporting Papuas Independence in Bandung City - Wicaksono, Rendi Armi Hadi; Gunawan, Budi; Ratmono, Barito Mulyo (Universitas Syiah Kuala, 2025)
This study explores the role of social media, specifically Facebook, in spreading propaganda related to the Papuan independence movement in Bandung. The research focuses on the Imasepa'bjb Facebook account, a significant platform used by Papuan students to promote Papua's independence. The study investigates how digital propaganda affects public opinion, mobilizes support for separatist movements, and poses a potential threat to national security and social order in Indonesia. Social media platforms like Facebook have become key tools for disseminating separatist ideologies, with emotional storytelling and strategic use of historical narratives aimed at galvanizing support for Papua Merdeka. The research utilizes a qualitative approach, including interviews with key informants and a review of online activities, to understand the implications of online activism on local security dynamics. By comparing digital propaganda techniques with earlier studies on media and propaganda, the study aims to fill a gap in understanding how these online movements influence the Papuan student movement in Bandung. The findings reveal that the Imasepa'bjb Facebook account has successfully shaped discourse among Papuan students, fostering a sense of solidarity and reinforcing the call for independence. These activities are not only a challenge to the governments policies but also a growing threat to Indonesia's national security. Recommendations include enhancing intelligence capabilities, strengthening counter-propaganda measures, and fostering positive narratives to engage Papuan students and reduce separatist sentiment. The study underscores the need for comprehensive monitoring and early intervention in the face of evolving digital threats.Keywords: Papua Merdeka, Imasepa'bjb, Facebook, social media propaganda, Papuan student movement, national security, separatist movements.